CPC-031 Clinical Trials Quality: Medical Journal Publication Involvement. (12th March 2013) - López García, B; Ortonobes Roig, S; Espona Quer, M; Florit Sureda, M; Barrantes Gonzalez, M; Salas, E
Abstract : Background: Clinical Trials (CTs) resulting in publication in biomedical journals is a strategy to guarantee good quality research. Clinical research promoters are obligated to publish either positive or negative results; regretfully this good practise is not as common as it should be. Cardiology and Oncology boards are the two services carrying on the highest number of CTs in our hospital. Purpose: To cheque the CT publication index carried out by Cardiology and Oncology Clinical Services, to analyse the journals' impact factor (IP) where CTs have been published. Finally we evaluated if the published results were positive or negative. Materials and Methods: A retrospective observational study has been carried out considering all data within the period from 2002 and 2007, in the pharmacy CT unit. The study only assessed open clinical trials of Cardiology and Oncology services. A systematic search was performed of medical journals indexed in PubMed and Clinicaltrials.gov databases until Oct. 2012. The following variables were collected for each CT: code, journal, publication data, IP and CT results. Every CT not proving the hypothesis described in the initial protocol was considered to be a negative result (NR). Results: 229 CTs were analysed. CT/medical specialty: oncology 168 (73.4%), cardiology 61 (26.6%). CTs already closed: Oncology 85 CTs (50.6%), cardiology 46 (75.4%). CTs already published: 61 (26.4%), oncology 22 (36.1%), cardiology 39 (63.9%). CTs published with positive results: (43 CTs) 70.5%. Oncology 17 (77.3%), Cardiology 26 (66.7%). CTs were published in journals with IP between 2.022 and 53.298. Mean IP was 18.479 (17.406 SD). Conclusions: Fewer than 26.4% of clinical trials initiated in the two Medical Services have been published. A high percentage of CTs initiated have never been published. Only 29.5% of all published CTs were published with a NR. This may suggest a low level of NRs result in journal publication. The Publication IP ranges widely between low and high scores. Nevertheless we consider the mean IP to represent a high standard of publication. No conflict of interest.